2015
DOI: 10.1093/hmg/ddv112
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of blood lead shows multiple associations near ALAD

Abstract: Exposure to high levels of environmental lead, or biomarker evidence of high body lead content, is associated with anaemia, developmental and neurological deficits in children, and increased mortality in adults. Adverse effects of lead still occur despite substantial reduction in environmental exposure. There is genetic variation between individuals in blood lead concentration but the polymorphisms contributing to this have not been defined. We measured blood or erythrocyte lead content, and carried out genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 57 publications
2
33
0
1
Order By: Relevance
“…Variation in rs1800435, which has been reported to alter susceptibility to lead poisoning,11 did not modify the association between lead exposure and kidney cancer in our study, the study by van Bemmel et al ,10 nor in the nested case-control study of Finnish smokers by Southard et al 6. Our analysis of rs1805313, which was recently associated with blood lead in a GWAS,12 was similarly null. Although we cannot rule out the existence of subtle patterns of interaction given study power limitations, our findings do not support the existence of lead-kidney cancer effect modification by ALAD variants.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Variation in rs1800435, which has been reported to alter susceptibility to lead poisoning,11 did not modify the association between lead exposure and kidney cancer in our study, the study by van Bemmel et al ,10 nor in the nested case-control study of Finnish smokers by Southard et al 6. Our analysis of rs1805313, which was recently associated with blood lead in a GWAS,12 was similarly null. Although we cannot rule out the existence of subtle patterns of interaction given study power limitations, our findings do not support the existence of lead-kidney cancer effect modification by ALAD variants.…”
Section: Discussionsupporting
confidence: 45%
“…Findings from one study suggest that kidney cancer and lead association are modified by single nucleotide polymorphisms (SNPs; rs8177796 and rs2761016) mapping to ALAD , which encodes a haem biosynthesis enzyme (5-aminolevulinic acid dehydratase)10 implicated in lead-induced anaemia toxicity 11. Another ALAD SNP, rs1805313, has been significantly associated with blood lead levels in a genome-wide association study (GWAS);12 this variant has not been evaluated as a possible effect modifier for lead exposure and kidney cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The neurotoxic mechanisms of lead encompass effects on the composition and function of hippocampal NMDA receptors ( Neal and Guilarte 2010 ; Neal et al 2011 ) and inhibition of presynaptic calcium channels ( He et al 2009 ). Previous studies measuring lead blood or bone levels in human populations identified polymorphisms in ALAD encoding δ-aminolevulinic acid dehydratase, associated with heme biosynthesis; VDR , which encodes the vitamin D receptor; and the hemochromatosis-associated gene HFE ( Onalaja and Claudio 2000 ; Warrington et al 2015 ; Jhun et al 2015 ). In addition, lead-dependent changes in DNA methylation in mice ( Sánchez-Martín et al 2015 ) have been documented, and Li et al (2015) identified associations between human lead blood levels in childhood and DNA methylation in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research shows that higher amount of Pb in human body associated with hypertension, reproduction disorder, and renal disfunction [8,9]. Every individual has the ability to control the metabolism of Pb with ALAD gene.…”
mentioning
confidence: 99%